Terrestrial palaeo-environmental proxy data of the Upper Pliensbachian, Mochras Borehole sediments, deposited in the Cardigan Bay Basin, Wales - Hollaar, Teuntje (NERC EDS National Geoscience Data Centre, 2021)
Terrestrial palaeo-environmental proxy data has been collected to examine orbital changes in wildfire activity in the Early Jurassic of the Mochras Borehole, Cardigan Bay Basin, Wales. To do this a high resolution charcoal abundance dataset was created and quantified in two size fractions, microscopic charcoal (10-125 µ) and macroscopic charcoal (>125 µ). To take potential changes in riverine influx and/or organic preservation in account on the charcoal abundance, palynofacies were analysed to document all terrestrial and marine organic particles present in the samples, and next to this, X-ray fluorescence data was gathered to assess detrital output. Mass spectrometry provided information on the carbonate and Total Organic Carbon content and bulk organic carbon isotopes. This information was used to look at changes in the lithology and the carbon cycle. Finally, clay mineralogical data was obtained to look at changes in the hydrological cycle in relation to wildfire activity.
This dataset spans 951-934 mbs from the Mochras borehole, which is the time equivalent of ~350 kyr, in the Margaritatus Zone of the Upper Pliensbachian. The Mochras sediments have been deposited in the Cardigan Bay Basin, Wales. At the time of deposition, this location was positioned in the Laurasian Seaway at a paleolatitude of ~35°N.
These datasets were obtained at a high resolution (10 cm) using X-ray diffraction, X-ray fluorescence, mass spectrometry and palynological preparations. This high resolution was acquired to analyse the presence of precessional orbital forcing on wildfire and the other proxy datasets.
This data was collected, interpreted and analysed by Teuntje Hollaar, Claire Belcher, Stephen Hesselbo, Micha Ruhl, Jean-Franҫois Deconinck, Sarah Jane Baker and Luke Mander. The complete dataset presented in the published article file ‘Wildfire activity enhanced during phases of maximum orbital eccentricity and precessional forcing in the Early Jurassic’ has been included in this data file.
Keywords: charcoal; Palynofacies; clay mineralogy; X-ray fluoresence; mass spectrometry; bulk organic carbon isotopes